Age comorbidity scores as risk factors for 90‐day mortality in patients with a pancreatic head adenocarcinoma receiving a pancreaticoduodenectomy: A National Population‐Based Study. (2nd December 2019) - Shia, Ben‐Chang; Qin, Lei; Lin, Kuan‐Chou; Fang, Chih‐Yuan; Tsai, Lo‐Lin; Kao, Yi‐Wei; Wu, Szu‐Yuan
Abstract: Background: To estimate easily assessed preoperative factors for predicting 90‐day mortality in patients with a pancreatic head adenocarcinoma (PHA) receiving a pancreaticoduodenectomy. Methods: We analyzed data from the Taiwan Cancer Registry Database of patients with a PHA who received a pancreaticoduodenectomy. Basic demographic characteristics, including gender and age, were categorized. The selection of preoperative comorbidities was based on the preoperative American Society of Anesthesiologists score and Charlson comorbidity index. Results: We enrolled 8490 patients with a PHA who received a pancreaticoduodenectomy without distant metastasis. Currently, a pancreaticoduodenectomy for a PHA achieves an overall 90‐day mortality rate of 8.39%. Univariate and multivariate Cox regression analyses indicated that an older age (65‐74 and ≥75 years) and specific comorbidities (chronic obstructive pulmonary disease, chronic kidney disease, dementia, and sepsis) were significant independent prognostic factors for predicting 90‐day mortality after a pancreaticoduodenectomy. After adjustment, the adjusted hazard ratios (aHRs) (95% confidence intervals [CIs]) of subjects with middle and high comorbidity scores for 90‐day mortality in 65 to 74‐year‐old patients were 1.36 (1.05‐1.75) and 2.25 (1.03‐4.90), respectively, compared to subjects with low comorbidity scores. The aHRs (95% CIs) of subjects with middle and high comorbidity scores for 90‐day mortality in ≥75‐year‐old patients were 1.35 (1.07‐1.78) and 2.07 (1.19‐3.62), respectively, compared to those with low comorbidity scores. Conclusions: Elderly patients with a PHA and moderate or high comorbidity scores have an increased risk of 90‐day mortality after a pancreaticoduodenectomy. Abstract : This is the first study to utilize the largest cohort of patients with pancreatic head adenocarcinoma and to develop an easily implementable tool using preoperative characteristics such as age‐comorbidity predictive scores for 90‐day mortality in patients with pancreatic head adenocarcinoma receiving pancreaticoduodenectomy.